EARLY CONGENITAL SYPHILIS: CLINICAL AND LABORATORY FEATURES IN THE NEONATAL PERIOD - N. V. Matyskina; T. E. Taranushenko; V. I. Prokhorenkov (LLC "Diagnostics and Vaccines", 2015)
Syphilis remains one of the very disturbing inflections. The highest morbidity rate is registered among women at the age of 18-29 years old. The percentage of pregnant women in the General statistics of syphilis incidence is 8 to 12%. Against this background, the syphilis incidence among newborn infants is an extremely serious problem. The article presents the clinical case of early congenital syphilis in the newborn baby.